Neuropathy and neuroarthropathy as a complication of diabetes and other diseases, with particular emphasis on painless fractures - a review of the literature - Michal Oleszko; Kamila Fularska; Aleksandra Kuźniar; Dominik Szawica; Edward Wąsiewicz; Radosław Bernacki; Piotr Bernacki; Martyna Dutka; Witold Zardzewiały (Kazimierz Wielki University, 2023)
Diabetes is now one of the most common chronic diseases. Its incidence is increasing, and thus the number of people suffering from its health complications is increasing. In 2015, 3 million people in Poland suffered from diabetes, and it is estimated that this number will increase to 4 million by 2040. Acute complications of diabetes include i.a. hypoglycemic or lactate and hypermolar comas. Chronic complications include, for example, microangiopathies (retinopathies, nephropathy) as well as macroangiopathies and neuropathies. Neuropathy is the result of too much glycemia and can affect as many as 2/3 of diabetic patients. Everyday pain sometimes makes it impossible to perform the simplest activities, and an optimal treatment plan is difficult to develop. At the same time, it can be prevented with regular exercise, regular glycemic control and a proper diet. In this paper, we present a literature review on neuropathy and neuroarthropathy as a complication of diabetes and other diseases, with particular emphasis on painless fractures.